High-risk human papillomavirus cervical infection prevalence: a nationwide retrospective study comparing opportunistic and organised screening, France, 2020 to 2023 - Samuel Alizon (Eurosurveillance)
BACKGROUND In France, cervical cancer screening for females aged 30–65 years primarily tests for high-risk (HR) human papillomavirus (HPV) infections. AIM We aimed to map the prevalence of cervical infections caused by HPV16 and/or 18, or by any of 12 other carcinogenic HPV genotypes and compare prevalence estimates from tests from spontaneous medical visits (opportunistic screening) or the national screening programme (organised screening). METHODS We extracted data from a large network of biology laboratories, containing all available results from HR HPV tests performed between 1 January 2020 and 30 November 2023 in metropolitan France. A full hierarchical Bayesian model was used to compute spatially resolved expected prevalence maps at the postcode level. RESULTS The analytic sample contained results of 362,963 HR HPV tests. Among samples positive for HPV16 and/or 18, 2.9% and 3.8% were from organised and opportunistic screening, respectively. Samples positive for other genotypes were 6.9% and 9.4%, respectively. During the last week of the study (week 48 2023), among females aged 30 years, opportunistic screening was associated with a greater expected prevalence of HPV16 and/or 18 and other genotypes in 97.2% and 99.9% of postcodes, respectively. The probability this percentage was lower among females aged 66 years was below 95% for both genotype groups. For organised screening, a pronounced north-west/south-east gradient in infection prevalence was found across France for both genotype groups, with hotspots located at the border with Italy, Spain and Switzerland. CONCLUSION Opportunistic screening is associated with systematic inflation of HR HPV infection prevalence.